2017
DOI: 10.1111/ens.12245
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the tribe Erotini with description of a new genus from China (Coleoptera: Lycidae)

Abstract: Erotini is a small tribe of net‐winged beetles known from the northern temperate zone. We investigated relationships and limits of tribes and genera using a molecular phylogeny inferred from rrnL, cox1 and nad5 mtDNA fragments. Lopheros Leconte, 1881 and Pseudaplatopterus Kleine, 1940 were inferred in current molecular analyses as terminal lineages within Erotini. Therefore, we consider Lopherotini Kazantsev, 2012 and Pseudaplatopterina Kazantsev, 2012 as junior synonyms of Erotini Leconte, 1881. The Platycis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…of ∼160 spp. worldwide), one of the three earliest lineages of the family (Kusy et al ., 2019) that is most diverse in the temperate Holarctic and uncommon in the tropics (Kazantsev, 2004; Li et al ., 2017; Masek et al ., 2018). Other groups, the Calochrominae (6 spp.)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…of ∼160 spp. worldwide), one of the three earliest lineages of the family (Kusy et al ., 2019) that is most diverse in the temperate Holarctic and uncommon in the tropics (Kazantsev, 2004; Li et al ., 2017; Masek et al ., 2018). Other groups, the Calochrominae (6 spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Kusy et al (2019) redefined subfamilies and tribes using phylogenomic data, and Motyka et al (2021b) built the phylogeny of >500 species, i.e., about 12% of world fauna utilizing the combination of the phylogenomic backbone and Sanger data. The DNA data on Chinese fauna were reported by Li et al (2015Li et al ( , 2017, Motyka et al (2017), and Kusy et al (2021). We add further sequences for the Western Palearctic species.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although their colonization capacity has not been studied, the earlier published phylogenies have shown that net-winged beetle faunas with high species turnover can be separated by narrow sea straits (Malohlava & Bocak, 2010; Li, Bocak & Pang, 2015a; Li et al, 2015b; Li, Pang & Bocak, 2017b; Masek et al, 2018) and only some flower-visiting net-winged beetles are more effective colonists (Motyka, Masek & Bocak, 2017). Due to biological characteristics, Cautires have a lower dispersal capacity than long living, well-sclerotized and well-flying beetles such as water or dung beetles (Balke et al, 2009; Masek et al, 2014, 2015; Toussaint et al, 2015; Li, Pang & Bocak, 2017a ; Bocek et al, 2018). The genus was supposedly brought to Asia with drifting India 35–55 mya, its diversification started before the colonization of the Sunda Shelf and resulted in ∼170 described species from the Oriental region (Kleine, 1933; Bocak, 2002; Dudkova & Bocak, 2010; Sklenarova, Chesters & Bocak, 2013; Sklenarova, Kubecek & Bocak, 2014).…”
Section: Introductionmentioning
confidence: 99%